Stent crush: A novel endovascular approach for treatment of complex in‐stent femoropopliteal chronic total occlusion. Issue 2 (16th July 2019) - Tabaza, Luai; Janzer, Sean; George, Jon C.
Abstract: Femoropopliteal in‐stent chronic total occlusions (CTOs) remain one of the most challenging subsets of peripheral arterial disease to treat percutaneously. Advances in available CTO crossing technology and operator experience have increased percutaneous intervention success rates. We report a case of critical limb ischemia in a patient with chronically occluded femoropopliteal nonoverlapping stents treated with a novel percutaneous approach of subintimal retrograde angioplasty using high compression resistant nitinol stents to crush the occluded previous stents to create a neo‐lumen.